Long Term Health Problems and Associated Factors among COVID-19 Recovered Patients - Sarker, Abu Kawser; Alam, Kazi Shafiul; Ema, Fateha Akter; Ali, Md Yunus (Community Based Medical Journal, 2024)
A cross-sectional, descriptive study was conducted among 181 individuals recovered from COVID-19 infection and had been missing infection (negative rt-PCR test) or signs-symptoms for minimum three months. The study aims determine newly developed health problems in patients, which was conducted at Post-COVID Unit of Anwer Khan Modern Medical College Hospital, Dhaka, Bangladesh, between July 2021 and June 2022. Through convenient sampling, data were collected by face-to-face interview and history of signs/ symptoms during the infection were recorded from reviewing prescription and interview as well by using a semi-structured questionnaire. The mean age of the participants was 39.56±6.92 years and male-female ratio was 1.45:1. The mean monthly family income of the participants was 36,022.09±4130.56 BDT which represents lower middle to middle class family in terms of Bangladesh context. During COVID-19 infection most of the (97%) respondents had fever, and 87%, 79% of the patients had sore throat and cough respectively as common symptoms; in addition, more than one-third (34%) had diarrhea. Several constitutional symptoms also recorded during their course of illness like headache (74%) and malaise (54%). More than one-third (34%) of the respondents required admission in hospital. During the course of infection, 41%, 26% and 31% participants were suffered from mild, moderate and severe form of COVID-19 illness. Most of the respondents developed long term health problems following COVID infection and post-viral fatigue was the most prevalent (85%) among the post COVID individuals and this long-term health problem-post viral fatigue was found to be associated with monthly income and it was statistically significant (p<0.05). Others long term health problems including shortness of breath (74%), loss of memory (38%), difficulty in concentration (41%), loss of hair (30%), fast beating or pounding heart (33%) were also noticed. Insomnia (56%), persistent cough (35%), loss of taste (32%) and change of bowel habit (28%) were other health problems revealed in this study. Association between loss of memory and gender (p<0.0001), diabetes mellitus and severity of COVID-19 (p<0.05), sore throat, cough and severity of COVID-19 (P<0.05) were also found significant. diabetes mellitus (35%), hypertension (34%) and bronchial asthma (24%) were observed to be most common comorbidities. Shortness of breath – one of the post-COVID consequence was found significantly associated with diabetes mellitus and bronchial asthma (p<0.05). Our study found that persistence of various signs and symptoms from COVID-19 infection and newly yield complications in individual who recovered from COVID-19 infection are collectively comprise long term health problems of post-COVID patients. This long-term health problem of post-COVID people is a major public health concern. Fatigue, dyspnea, difficulty to concentrate, memory loss, persistent cough, fast beating or pounding heart, loss of smell, loss of taste, insomnia are the most common long term health problems in COVID-19 recovered people. Long-term follow up may be recommended to understand future consequences of COVID-19 patients and well-being for the post-COVID people. CBMJ 2024 July: vol. 13 no. 02 P: 158-168